National Police Research Platform, Phase I (United States), 2009-2011 - McDevitt, Jack ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed.The National Police Research Platform was designed to a) strengthen the science of policing by generating timely, in-depth, longitudinal information about policing organizations, personnel and practices and, b) move policing in the direction of evidence-based "learning organizations" by providing translational feedback to police agencies and policy makers. Phase I focused on testing methods and measures in 29 agencies in order to build the Platform infrastructure. First, a "total department" online methodology was successfully implemented covering numerous dimensions of organizational behavior, from supervision and accountability to employee integrity and burnout. Second, a public satisfaction contact survey was implemented in several jurisdictions to provide local external indicators of the quality of police-citizen encounters and organizational legitimacy in the community. Third, two longitudinal studies were initiated - one of new police recruits and one of new first-line supervisors - to chart their career development and identify factors that influence life trajectories. Finally, a randomized control trial was introduced in once site to test the effects of procedural justice training as part of the Platform's measurement system.